2012
DOI: 10.5815/ijmecs.2012.11.08
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of E-assessments System on the Success of the Implementation Process

Abstract: -This study aims to identify the attitudes of the sample individuals from students that have used the electronic assessments (e-assessments) system at Isra University in Jordan. These attitudes describe the relationship between the availability of the requirements for e-assessments applications and the success of its implementation. Analytical descriptive method and sample research have been used. The samples included 246 students from 5 colleges covered by the research sample. The instrument of the study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 5 publications
2
14
0
3
Order By: Relevance
“…The paper test consumes time from teacher to correct each paper, but using E-assessment will save the teacher time [7], [8], [14], [15], [19], [21], [22], for example, in Leeds Metropolitan University research they found that E-assessment saved up to £3000 per cohort in staff time. Also, E-assessment helps the teacher to improve the quality of feedback for the students [8], [16].…”
Section: B Teachermentioning
confidence: 99%
See 1 more Smart Citation
“…The paper test consumes time from teacher to correct each paper, but using E-assessment will save the teacher time [7], [8], [14], [15], [19], [21], [22], for example, in Leeds Metropolitan University research they found that E-assessment saved up to £3000 per cohort in staff time. Also, E-assessment helps the teacher to improve the quality of feedback for the students [8], [16].…”
Section: B Teachermentioning
confidence: 99%
“…It is, also, fast and easy to use [13], [14]. E-assessment provides immediate feedback comparing with paper test, which helps to improve the learning level [7], [8], [15], [16].…”
Section: The Advantages Of Usinf E-assessmentmentioning
confidence: 99%
“…JISC (2007) defines E-assessment as the end-to-end electronic assessment process, where ICT (Information Communication Technology) is used for the whole assessment processes from the presentation of questions to the saving of the learners' responses. E-assessment has advantages compared with paper-test, in terms of saving time consumed for the tutor to correct each paper (Crews & Curtis, 2010;Donovan et al, 2007;Eljinini & Alsamarai, 2012;Gikandi, Morrow, & Davis, 2011;Gilbert et al, 2011;Ridgway et al, 2004;Sorensen, 2013). For example, in study at Leeds Metropolitan University it was found that E-assessment saved up to £3000 per cohort in staff time (Gilbert et al, 2011).…”
Section: Litereture Reviewmentioning
confidence: 99%
“…Thus, lecturers should have adequate time to use this form of assessment, and also have access to the money and technology needed to use E-assessment. Eljinini & Alsamarai (2012) found that the availability of infrastructure impacts the success of E-assessment implementation. The importance of the infrastructure factor in establishing an E-assessment system is also highlighted by Way (2012).…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation